A multilevel UPQC for voltage and current quality improvement in distribution system - Nagi Reddy, Varampati Veera; Kumar, D.V Ashok; Kota, Venkata Reddy (Institute of Advanced Engineering and Science, 2019)
Unified Power Quality Conditioner (UPQC) is substantial power conditioner in power system to filter the power system parameters with an objective to improve the quality of power delivered to the customers/utility point. This paper presents a multi-level UPQC to enhance the quality in power distribution system. The series and shunt controllers of UPQC gives out five leveled output which is further filtered to feed compensating signals to improve voltage and current profiles in power distribution system. Series and shunt controllers of UPQC are structured with cascaded H-Bridge (CHB) topology to deliver compensating signals. Two separate control strategies are employed to regulate the power switches of 5-level CHB series and shunt controllers of UPQC. Sag and swell in source voltage and harmonics in source current are strained with UPQC. The proposed system is developed and results are obtained using MATLAB/SIMULINK software.